Cost-Effectiveness of Pharmacological Treatments for Osteoporosis Consistent with the Revised Economic Evaluation Guidelines for Canada. Issue 1 (January 2019) - Coyle, Doug
Introduction. Given the lack of independent analyses comparing numerous pharmacotherapies for osteoporosis, the study objective was to identify the optimal osteoporosis treatment based on a woman's age, fracture history, and ability to tolerate oral bisphosphonates adopting practices recommended in the recently revised Canadian guidelines.Methods. A cost utility analysis from the health care system perspective compared alendronate, etidronate, risedronate, zoledronate, denosumab, and no pharmacotherapy using a Markov model incorporating data on fracture risk and their associated costs, mortality, and disutility and treatment effect. Stratified analysis was conducted based on age, fracture history, and ability to tolerate oral bisphosphonates. Expected lifetime outcomes were obtained through probabilistic analysis with scenario analyses addressing methodological and structural uncertainty.Results. For women able to tolerate oral bisphosphonates, risedronate and etidronate were dominated. Compared to no therapy, alendronate was either dominant or was associated with a low incremental cost per QALY (quality-adjusted life years) gained (ICER)—less than CAN3, 751 based on age and fracture history. In comparison with alendronate, both zoledronate and denosumab were either dominated or associated with a high ICER—greater than CAN660, 000 per QALY. For women unable to tolerate bisphosphonates, dependent on age and fracture history, the ICER for zoledronate versus no therapy ranged from CAN17, 770 to CAN94, 365 per QALY. For all strata, denosumab was dominated by zoledronate or had an ICER greater than CAN3.0 million. Scenario analyses found consistent findings.Conclusions. Based on a threshold of CAN50, 000 per QALY, alendronate is optimal for osteoporotic women who can tolerate oral bisphosphonates regardless of age or fracture history. For women unable to tolerate oral bisphosphonates, zoledronate is optimal for women with previous fracture or aged 80 to 84 or over 90 with no previous fracture.